A Tiered Mentorship Program to Integrate Medical Students Into Clinical Research Projects. Issue 5 (May 2023) - Misiaszek, Shannon R.; Blitzer, David; Drucker, Charles B.; Endicott, Kendal M.; Fitzpatrick, Suzanna S.; Toursavadkohi, Shahab; Nagarsheth, Khanjan H.
Objective: Herein we describe the development, implementation, and growth of our Vascular Research Training Program (VRTP), emphasizing the intentional involvement of medical students in clinical research. Methods: We developed a VRTP focusing on medical student engagement to encompass 4 pillars: ownership, mentorship, experience, and independence within the research process. The program is organized by clinical projects with an attending surgeon, surgical trainee (fellow or resident), and medical student comprising each research project team. The VRTP program sought to facilitate a culture of learning, accountability, and mentorship to engage and encourage medical student involvement in clinical research. Results: We reviewed the productivity of our current vascular surgery faculty by reviewing divisional records of faculty publications and conducting a literature search for the period of 2012 to 2019. The pre-VRTP model produced 13 included manuscripts in 2012-2015 (3.25 per year), while the implemented VRTP model yielded 43 articles (10.75 per year) from 2016-2019. There was no significant change in the impact factor (pre-VRTP mean ± SD was 1.8 ± 1.0 vs 2.2 ± 1.1, P = .17). Medical student productivity rose from 1.3 to 2.7 publications, with a similar rise in the number of students participating in more than one manuscript from 2 to 14. Conclusions: Deliberate involvement of medical trainees as a member of the clinical research team has the potential to generate subsequent increases in research productivity and effective mentorships. Academic surgical divisions should consider organized and intentional involvement of medical students as an essential component of clinical research.